Implementasi Sanksi Adat Terhadap Pelanggaran Hukum Adat di Kabupaten Batang Hari - Umar Hasan; Sasmiar Sasmiar; Suhermi Suhermi (CV Rewang Rencang, 2025)
The purpose of this study is to examine and analyze whether the implementation of customary sanctions can realize justice, foster harmonization, and provide a deterrent effect for the perpetrators. The research problems focus on whether the application of customary sanctions can achieve justice and harmonization within the community, and whether the imposition of such sanctions can create a deterrent effect on the offenders. The research method employed is empirical juridical, analyzing primary data obtained through field research. The results of the study show that the enforcement of customary sanctions against violators of customary law in Kubu Kandang and Jembatan Emas Villages, Batang Hari Regency, is genuinely implemented through customary court sessions, where offenders are sanctioned according to the prevailing local customary law. This process has successfully realized justice and harmonization within the community. Furthermore, the imposition of customary sanctions has created a deterrent effect, particularly on the offenders and the broader community, as evidenced by a decrease in violations of customary law in Kubu Kandang and Jembatan Emas Villages, Batang Hari Regency.